2005
DOI: 10.1097/01.jcp.0000186901.79861.e2
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Case Series on the Use of Quetiapine for Posttraumatic Stress Disorder in Juveniles Within a Youth Detention Center

Abstract: Juveniles within the youth justice system have high rates of psychiatric morbidity, including posttraumatic stress disorder (PTSD). This case series describes 6 young people aged 15 to 17 years within a youth detention center who met the criteria for PTSD and reported an improvement in symptoms after 6 weeks of treatment with low-dose quetiapine. The primary outcome measure used was the Traumatic Symptom Checklist in Children. The dose of quetiapine ranged from 50 to 200 mg/d; T scores for PTSD symptoms decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The use of quetiapine for the treatment of child and adolescent PTSD was assessed in a case series carried out by Stathis et al [44] with the following setup: The subjects in this case series were 6 boys with a mean age of 16.7 years (SD, ±0.7). Of the 2 identified themselves as aboriginal or Torres Strait islanders, and 1 as Maori.…”
Section: Reviews On Psychopharmacotherapy Of Ptsd Among Children and mentioning
confidence: 99%
“…The use of quetiapine for the treatment of child and adolescent PTSD was assessed in a case series carried out by Stathis et al [44] with the following setup: The subjects in this case series were 6 boys with a mean age of 16.7 years (SD, ±0.7). Of the 2 identified themselves as aboriginal or Torres Strait islanders, and 1 as Maori.…”
Section: Reviews On Psychopharmacotherapy Of Ptsd Among Children and mentioning
confidence: 99%
“…The empirical literature is dominated by case studies/series, nonrandomized, and non-placebo-controlled studies on the use of quetiapine (Ahearn, Mussey, Johnson, Krohn, & Krahn, 2006;Filteau, Leblanc, & Bouchard, 2003;Robert et al, 2005;Hamner, Deitsch, Brodrick, Ulmer, & Lorberbaum, 2003;Sokolski, Denson, Lee, & Reist, 2003;Stathis, Martin, & McKenna, 2005), olanzapine (Butterfield, 2003;Izrayelit, 1998;Jakovljevic,Šagud, & Mihaljevic-Peleš, 2003;Labbate & Douglas, 2000;Petty, Brannan, & Casada, 2001;Pivac, Kozaric-Kovacic, & Mück-Šeler, 2004;Prior, 2001), risperidone (David, De Faria, Lapeyra, & Mellman, 2004;David, De Faria, & Mellman, 2006;Kozaric-Kovacic, Pivac, Mück-Šeler, & Rothbaum, 2005;Krashin & Oates, 1999;Monnelly & Ciraulo, 1999;Monnelly, Ciraulo, Knapp, & Keane, 2003), aripiprazole (Lambert, 2006), ziprasidone (Siddiqui, Marcil, Bhatia, Ramaswamy, & Petty, 2005), and clozapine (Hamner, 1996). To date, there are only a handful of published studies examining the efficacy of atypical antipsychotics utilizing a double-blind, placebo-controlled, and randomized design, and they have focused on risperidone (Bartzokis, Lu, Turner, Mintz, & Saunders, 2005;Hamner, Faldowski, et al, 2003;Monnelly et al, 2003;Reich, Winternitz, Hennen, Watts, & Stanculescu, 2004) and olanzapine (Butterfield et al, 2001;Stein, Kline, & Matloff, 2002).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…[40][41][42] However, even these small, uncontrolled studies have consistently found the development of significant side effects including weight gain among treated youth. Given the risk of obesity among trauma exposed youth in both childhood and adulthood, the availability of other medications without the significant risk of weight gain, and the lack of evidence supporting the use of SGAs, there is little role in the use of SGAs among most children with PTSD.…”
Section: Other Medicationsmentioning
confidence: 99%